The Interaction of Amiodarone and Continuous-flow Left Ventricular Assist Device Use in Risk of Severe Primary Graft Dysfunction Following Heart Transplantation. Issue 2 (13th January 2022) - Chinnadurai, Thiru; Patel, Snehal R.; Saeed, Omar; Hanif, Waqas; Rivas-Lasarte, Mercedes; Farooq, Muhammad; Castillo, Carolyne; Taveras, Maria; Fauvel, Daphenie; Shin, Jooyoung J.; Sims, Daniel; Murthy, Sandhya; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Primary graft dysfunction (PGD) increases morbidity and mortality after heart transplant. Here we investigated (1) the association of continuous-flow left ventricular assist device (CF-LVAD), amiodarone, and severe PGD and (2) the safety of amiodarone discontinuation in CF-LVAD patients. Methods: Retrospective, single-center study of heart transplant recipients was conducted to investigate the association of risk factors and severe PGD. Patients were grouped into 4 groups based on the presence (denoted +) or absence (denoted –) of amiodarone and CF-LVAD. Prospective amiodarone discontinuation was undertaken to investigate its safety in a cohort of CF-LVAD patients. Study endpoints were severe PGD and recurrence of arrhythmia. Results: Severe PGD was strongly associated with CF-LVAD and amiodarone use, and its prevalence is highest if both risk factors were present (CF-LVAD–/amiodarone – 1.5%, CF-LVAD –/amiodarone+ 4.5%, CF-LVAD+/amiodarone – 7.1%, CF-LVAD+/amiodarone+ 21.8%; P  < 0.01). The product of every 1-y additional CF-LVAD support by every 100 mg amiodarone was associated with severe PGD (adjusted odds ratio, 1.43; 95% confidence interval, 1.15-1.78; P  < 0.01). Amiodarone was prospectively discontinued in 28 CF-LVAD patients. Of them, 6 patients had recurrence of arrhythmia requiring treatment or heart failure admission. There were no deaths. Nine patients in whom amiodarone had been discontinued had heart transplants with no severe PGD. Conclusions: Amiodarone and CF-LVAD were independently associated with severe PGD. The combination of both risk factors was associated with a higher prevalence of severe PGD. Amiodarone discontinuation was associated with recurrence of arrhythmia in 6 CF-LVAD patients. There was no mortality associated with amiodarone discontinuation.